Effects of Propolis on Oxidative Stress in Rabbits Undergoing Implant Surgery - Ezgi Aydın; Ceylan Hepokur; Sema Mısır; Hasan Yeler (Cumhuriyet University, 2018)
Abstract Objectives: Implants are the natural or artificial materials that replace a missing tissue or organ. When that missing part is one or more teeth, there is a need for the reconstructive material that supports prosthetic restoration, which is called dental implant. Many local and general factors affect bone healing. Recent studies show that, free radicals are among the factors that affect the bone healing. This study is planned presuming propolis could have positive effects on oxidative stress and bone healing after implantation due to its antioxidant nature, its effects on accelerating the bone formation, wound healing and increasing the bone density. Materials and Methods: 24 New Zealand white rabbits were used in the study. Animals were divided into 3 groups, each consisting of 8 rabbits. Implants were placed into the proximal region of tibia unilaterally. Propolis was applied to slots before placing the implants on local group and systemically applied after implantation on systemic group. Results: SOD activity was increased in both propolis groups compared to control group, but it was not statistically significant. Catalase level of the systemic group was found to be significantly higher. MDA level in serum, which indicates lipid peroxidation, was significantly lower in both propolis groups compared to control group. Reduced GSH concentration in granulation tissue was increased in rabbit groups treated with propolis compared to control group. There were no significant differences in calcium and phosphorus values, however it can be said that there is a significant increase in vitamin D amount of local and systemic groups. Conclusion: Propolis has antioxidant, antimicrobial and many other biological activities. Due to the features that it has, propolis has a positive effect on osseointegration and bone healing. The comparison of systemic and local group showed that, systemically given propolis provided better results than local application.